Observing international relations : Niklas Luhmann and world politics - Albert, Mathias; Hilkermeier, Lena, 1971- (Routledge, 2004)
Observing International Relations draws upon the modern systems theory of society, as developed by Niklas Luhmann, to provide new perspectives on central aspects of contemporary world society.
Keywords: Luhmann, Niklas.; Luhmann, Niklas -- 1927-1998; Luhmann, Niklas, -- 1927-1998.; International relations -- Social aspects.; Relations internationales -- Aspect social.; POLITICAL SCIENCE -- Globalization.; International relations -- Social aspects; Weltpolitik; Weltgesellschaft; Systemtheorie; Internationale Politik; Relations internationales -- Sociologie.